Konsep Perlindungan Hukum Bagi Pembeli Tanah Dengan Bukti Kuitansi Melalui Pendekatan New Legal Realism - Roslina Mantolongi (CV. Era Digital Nusantara, 2025)
The phenomenon of land sale-and-purchase transactions supported solely by receipts without formal deeds prepared by Land Title Officials remains prevalent and places buyers in vulnerable positions owing to the lack of immediate certainty regarding the status of their property rights and the absence of comprehensive protection afforded by the land registration system. This research examines the legal protections available to buyers in such circumstances through a reexamination of positive law and judicial practice with the assistance of New Legal Realism perspective, which conceptualizes law as an interaction between written norms and social reality. The study employs normative legal research methodology utilizing legislative, conceptual, and case-based approaches directed toward the Agrarian Law (UUPA), Government Regulation No. 24 of 1997, the Indonesian Civil Code (KUHPerdata), and several relevant court decisions. Receipts are found to function primarily as evidence in civil proceedings regarding the fact of payment and the existence of a contractual relationship, whereas the recognition of property rights transfer is largely contingent upon the court's construction of good faith, principles of equity and fairness, and protection of the party who factually possesses and enjoys the land. Legal protections for buyers emerge through the possibility of filing an action for declaration of rights, a petition for cancellation of a subsequent transfer undertaken in bad faith, and the utilization of the principle of good faith in land registration. The New Legal Realism approach reveals the gap existing between formal procedures and customary practices in community transactions, and simultaneously directs recommendations for policy reform including the simplification of procedures, strengthening of legal education, and expansion of access to assistance for parties engaged in informal transactions.